2015
DOI: 10.1097/cej.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and mean platelet volume as potential biomarkers for early detection and monitoring of colorectal adenocarcinoma

Abstract: Colorectal cancer (CRC) is the third most common cause of cancer-related death in Europe. The aim of the present study was to elucidate the efficiency of the neutrophil/lymphocyte ratio (NLR), the platelet/lymphocyte ratio (PLR), and the mean platelet volume (MPV) as tools for the preoperative diagnosis of CRC and their usefulness in the follow-up of CRC. A total of 144 CRC patients, as diagnosed by colonoscopy, and 143 age-matched and sex-matched healthy participants were included in the study. Medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 39 publications
12
65
0
1
Order By: Relevance
“…It suggested that high preoperative levels of those parameters constituted a negative prognostic factor and reported a significant decrease after tumor resection, accompanied by a reduced CEA. 19 Likewise, the present study also detected, after tumor resection, a significant decrease in the whole patient group, whereas the decrease in MPV was limited to the relapse-free group. On the other hand, despite the absence of any significant change in NLR, PLR value displayed an upwards trend.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It suggested that high preoperative levels of those parameters constituted a negative prognostic factor and reported a significant decrease after tumor resection, accompanied by a reduced CEA. 19 Likewise, the present study also detected, after tumor resection, a significant decrease in the whole patient group, whereas the decrease in MPV was limited to the relapse-free group. On the other hand, despite the absence of any significant change in NLR, PLR value displayed an upwards trend.…”
Section: Discussionsupporting
confidence: 52%
“…[23][24][25] Among the studies examining the prognostic value of MPV in patients with CRC, a study on operated patients with CRC reported a higher MPV level for those patients compared to the control group, which fell significantly after tumor resection, and this decrease was associated with the reduced tumor burden. 19 Another study carried out a preopera- International Journal of Hematology and Oncology tive assessment for metastatic and non-metastatic patients, reporting higher MPV values for the former. The same study also found that, among metastatic subjects included, bevacizumab therapy was more beneficial for those with a lower MPV in terms of progression-free survival (HR: 0.41).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Wolfswinkel et al [12] argued that evaluation of NLR together with lymphocytopenia is more effective than studying CRP and total leukocyte count. Again, numerous studies suggested that NLR is an important criterion in making diagnostic and prognostic decisions in psoriasis, infective endocarditis, pneumonia, bacteremia and acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation is known to cause many cancer types, such as hepatocellular carcinoma derived from hepatitis B and C, gastric cancer derived from Helicobacter pylori, and colon cancer derived from inflammatory bowel disease (10). In the literature, platelet, C-reactive protein (CRP), interleukin-6 (IL-6), NLR, PLR, and RDW, all of which are considered markers of systemic inflammation, provide important clues about the early diagnosis and prognosis of colon cancer (6,(11)(12)(13). The activation of neutrophils, platelets, and macrophages contribute to chronic inflammation and lead to the increase of reactive oxygen species and reactive nitrogen intermediates, both of which have high mutagenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In inflammation, various mechanisms such as inflammatory cells, chemokines, cytokines, and proinflammatory mediators (cyclooxygenase and lipoxygenase) contribute to tumor cell formation, proliferation, and metastasis (5). Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and red blood cell distribution width (RDW) biomarkers reflect the systemic inflammatory condition in many cancer types, and they have been determined to be early diagnosis and prognostic factors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%